Touchez pas au grisbi - Wiéner, Jean 1896-1982 (<<The>> Criterion Coll., 2005)
An aging gangster is unwillingly brought out of retirement after one of his associates unwittingly betrays him to a rival.
Bildformat: 1.33:1 aspect ratio - New, restored high-definition digital transfer
Orig.: Frankreich, Italien 1954
Enth. 2002 video interview with actor Daniel Cauchy ; excerpt from an episode of the French television series "Cinéastes de notre temps" dedicated to Jacques Becker, featuring screenwriter Maurice Griffe, "Grisbi" author Albert Simonin, actor Lino Ventura, and François Truffaut ; 1972 interview excerpt with Lino Ventura ; clip from a 1978 interview with composer Jean Wiener ; Theatrical trailer ; new essay by critics Philip Kemp and Geoffrey O'Brien
Keywords: Vol - Drame; Gangsters -- France -- Drama; Frankreich; Feature films; Film adaptations; Foreign films - France; Gangster films; Motion pictures, French; Crime - Feature